LiveGene conversations on livestock genetics for development: Steve Kemp - Kemp, Stephen J. (International Livestock Research Institute, 2016)
LiveGene conversations on livestock development interview with Gabrielle Persley talking to Steve Kemp about ILRI's global livestock genetics program. Recorded in December 2015.